Fragmenta i testimonia hermetyczne u autorów różnych. Wstępny przegląd źródeł - Sowińska, Agata Ewa (Vox Patrum, 2020)
This contribution provides an insight into the history of Hermetic literature in the area of its influence on the literary sources of the ancient times and the Middle Ages. The article is a reference point for further research on the use of Hermetic literature in literary discourse ‒ especially within religious and philosophical themes.